Comparative analysis of multicriteria decision-making methods evaluating the efficiency of technology transfer - Kraujalienė, Lidija (Business, Management and Economics Engineering, 2019)
Purpose – to find appropriate tools to measure the efficiency of the technology transfer process (TTP) in higher education institutions (HEIs). Scientific problem is a lack of methods measuring the efficiency of TTP. The objective – comparative analysis of efficiency evaluation methods. Research methodology – the research methodology is based on a comparative analysis of the research papers on the advantages and disadvantages of methods suitable to evaluate the efficiency of TTP. Findings – among some tools, FARE is highlighted for identifying the variables of TTP and assigning their weights, when TOPSIS – to rank the variables and identify the most important. MULTO-MOORA and COPRAS methods with ranking abilities are suitable to select the number of HEIs. DEA method is intended for the economic evaluation of TTP efficiency in HEIs. The social sciences are strengthened by suitable founded tools to measure the efficiency of TTP in HEIs. Research limitations – this paper is providing all advantages and disadvantages (limitations) of decision-making multicriteria methods. Practical implications – the original structure of methods enabling stakeholders (HEIs, TTOs and public authorities) for efficient allocation of an organisation’s financial resources, foresee the future goals for improving the efficiency of TTP. Originality/Value – the original framework of methods incorporated into the one model, enabling related stakeholders (HEIs, TTOs and public authorities) allocate financial resources efficiently.